Mesenchymal Stem Cells injection in hip osteoarthritis: preliminary results - Carlo, Dall’Oca (Acta Biomed, 2019)
Background and aim of the work: Osteoarthritis will become even more common in the near future since the average life span is steadily growing. Pain and loss of function are the main complaints reported by patients, inevitably leading towards a worsened daily life performance. New modern techniques have been developed with advanced cell based therapies. Mesenchymal stem cells (MSC) have the inner ability to mature into different types of cells depending on the stimuli they undergo. This technique has already been proven successful in the knee and, with this retrospective study, we would like to assess its feasibility in the hip joint. Methods:6 consecutive patients affected by hip osteoarthritis were treated by intra-articular injection of autologous adipose-derived MSC between June 2017 and June 2018. Our study included only patients with constant hip pain resistant conservative treatment and OA graded 0-2 on the Tonnis grading scale. All 6 patients were evaluated in the preoperative setting and at the 6 months post-operative mark. Results: The HHS showed an improvement from the pre-operative baseline mean value of 67.2±3.4 to the 84.6±6.3 post-operative value. Moreover, the WOMAC score dropped from a baseline score of 36.3±4.7 to 19.8±3.4 at 6 months’ post-op follow up visit. Conclusions: MSC Lipogems is a fairly easy technique. No adverse effects were recorded in our experience. Preliminary results showed a positive outcome according to all the grading systems used in this study even though a longer follow up is needed to validate this technique. (www.actabiomedica.it)